Meet me in Hawaii - Toffolo, Georgia; Stewart, Rachael (London ; Mills & Boon an imprint of HarperCollinsPublishers Ltd., 2021)
"The perfect escapism. Romantic, sexy and full of sunshine' Lia Louis, bestselling author of Dear Emmie Blue 'Totally dreamy, funny in all the right places, and unabashedly romantic. I loved it!' - Laura Jane Williams, bestselling author of Our Stop 'So much fun it made me feel like I was actually on holiday with Toff... it was so full of heart and love. And I cried happy tears at the end. Jane Linfoot bestselling author of Love at the Little Wedding Shop by the Sea Where an ocean of love awaits Malie Pukui doesn't believe in happy ever after. After a tragedy caused her to flee her family and friends in Devon she found a fresh start in Hawaii. Here, working at a surf school, she can give back to those in need and try to overcome the greatest loss in her life. Moved around foster homes throughout his childhood, Todd Masters has worked hard to be able to offer a brighter future to young disadvantaged children. Now he has his own charitable foundation working with a surf school in Hawaii, a job he loves, but he still can't put his past behind him. When Malie rescues Todd from the sea a spark ignites between them, and the two wounded souls find a common ground. But amidst the surf, sunsets and sizzling kisses, can Malie let go of her past and risk something she'd locked away forever... her heart? A delightful burst of sunshine just when I needed it. Jules Wake, bestselling author of The Saturday Morning Park Run 'A beautiful and heartfelt story of joy and glorious escapism. The tonic we all need right now.' Alex Brown bestselling author of The Secret of Orchard Cottage 'Fun, friendship, heartbreak and the hope of love - all wrapped up in the most breathtaking scenery!"--Publisher's description
Keywords: English fiction; Man-women relationships -- Fiction; Surfing -- Fiction